Self-administration of the people of Sakha in Yakutian region from 17th to 19th century in context of imperial statehood - Nikitina, Sargylana E. (The New Research of Tuva, 2010)
The Russian civilization started to interact with the aboriginal traditional civilization in the Yakutian region by the 17th century, and by that time the potestas system was already formed within a common law in the Yakutian society. The clan aristocracy that received social privileges within the Russian statehood turned into an additional grass-roots level of government in the Yakutian district during the 17th-18th centuries.
Keywords: self-administration; alien self-administration; common law; ancestors; toyons; dukes; ulus; ulus heads; alien authorities; taxs; curatorship; people schools